Efficacy of Assessing Magmatic Storage Depth Using Natural Samples, Experiments and Thermodynamic Models: A Case Study From Valles Caldera, NM (USA) - Magdalen A. Grismer; Laura E. Waters; Gordon M. Moore; Gabriela A. Farfan (Geochemistry, Geophysics, Geosystems)
Abstract Estimates of magmatic storage are typically made using mineral assemblages in natural samples, experiments and thermodynamic models (e.g., MELTS), where each method has limitations. Here, we compare each of these methods to assess their utility in estimating storage conditions for post‐collapse, two‐feldspar high‐silica rhyolites (HSRs) sourced from Valles Caldera, NM (USA). We focus on the Valle Grande HSRs, which have known whole rock, glass compositions, crystallinities and storage conditions (∼750–770°C; ∼130–165 MPa). Equilibrium experiments that overlap with magmatic storage conditions determined from sample petrology have glass and mineral compositions that match those in the natural samples, suggesting that the phenocryst assemblage is accurately recording pre‐eruptive conditions. RMELTS reproduces differing aspects of the natural samples and experiments, but generally confirm storage conditions (751–758°C; 179–215 MPa) recorded by the petrology of the post‐collapse high‐silica rhyolites. RMELTS reproduces the experimentally determined phase‐in curves within ±5°C, at pressures >125 MPa. Below 125 MPa, RMELTS overpredicts the stability of the experimental quartz, sanidine and anorthoclase. We apply the RMELTS geothermobarometer to the Glass Mountain obsidians (two‐feldspar HSRs) to evaluate possible reasons for the agreement between RMELTS, experiments, and Valle Grande HSRs. The RMELTS geothermobarometer overpredicts the Glass Mountain obsidians' temperatures by 50–77°C, and likely underpredicts pressures. RMELTS predicts a common co‐saturation temperature of ∼750°C for these two HSRS. We find that RMELTS recovers the storage temperature and pressures for Valle Grande HSRS because they have temperatures of ∼750°C, contain <30% total crystallinity, are near equilibrium and are stored at >125 MPa.